2021
DOI: 10.1073/pnas.2024805118
|View full text |Cite
|
Sign up to set email alerts
|

Foam film stratification studies probe intermicellar interactions

Abstract: Ultrathin foam films containing supramolecular structures like micelles in bulk and adsorbed surfactant at the liquid–air interface undergo drainage via stratification. At a fixed surfactant concentration, the stepwise decrease in the average film thickness of a stratifying micellar film yields a characteristic step size that also describes the quantized thickness difference between coexisting thick–thin flat regions. Even though many published studies claim that step size equals intermicellar distance obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 108 publications
(215 reference statements)
6
52
0
Order By: Relevance
“…This observation, which also has previously been made for the case of other nonionic surfactants, 73 , 74 is in contrast to the variable Δ h systematically reported for ionic surfactants. 75 Regardless of the small Π osc , the Newton black film (NBF) that was formed at h < d was stable and did not break, even at the maximum pressure that can be applied in our setup (∼10 kPa). This is again in agreement with results on films stabilized by similar nonionic surfactants.…”
Section: Resultsmentioning
confidence: 81%
“…This observation, which also has previously been made for the case of other nonionic surfactants, 73 , 74 is in contrast to the variable Δ h systematically reported for ionic surfactants. 75 Regardless of the small Π osc , the Newton black film (NBF) that was formed at h < d was stable and did not break, even at the maximum pressure that can be applied in our setup (∼10 kPa). This is again in agreement with results on films stabilized by similar nonionic surfactants.…”
Section: Resultsmentioning
confidence: 81%
“…In summary, the analysis of foam stability requires the collection of a wide range of information from the nano-to the centimetre scale that has to be correlated for a better understanding of the underlying processes. While such a multi-scale analysis is mostly performed using different techniques separately in the literature 36,39 , herein the evolution of a foam has been followed simultaneously using macro-photography, electrical conductivity, and small-angle neutron scattering. The combination of these three techniques allows to perform this multiscale analysis in real time on a given sample.…”
Section: Discussionmentioning
confidence: 99%
“…A surfactant film is subjected to an external gas pressure and the difference with the capillary pressure causes the film to drain until the pressures are balanced 37 . The film thickness is then measured by interferometry as a function of the applied pressure to build a pressure isotherm allowing the experimentalist to quantify the interactions between facing interfaces 38,39 . However, these experiments are carried out on isolated films and the extrapolation of these observations to the evolution of the 3D structures such as liquid foams where other effects impact the drainage is far from trivial.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules form layered structures next to an interface or under confinement and contribute to disjoining pressure in the form of oscillatory structural forces like solvation forces that can be measured using techniques like surface force apparatus (SFA). , The structuring and the associated structural forces, manifested in both experiments and simulations, influence the stability, drainage, and topography of ultrathin films (thickness h < 100 nm) through the thickness-dependent disjoining pressure. , Analogous structuring of supramolecular structures like micelles, polymers, liquid crystals, and nanoparticles creates oscillatory structural forces in liquid films that are alternatively quantified as film thickness h -dependent supramolecular oscillatory disjoining pressure, Π OS ( h ). In freestanding films or foam films comprising supramolecular structures, an interplay of Π OS ( h ) and capillary pressure P c leads to drainage via stratification manifesting as stepwise thinning for ultrathin films ( h < 100 nm), wherein the step size Δ h is comparable to the thickness difference between coexisting thick–thin flat regions. , , , Experimental measurements with SFA and colloidal probe atomic force microscopy (CP-AFM) as well as simulations have shown that Π OS ( h ) periodicity is significantly greater than the size of charged micelles or particles. , , , Correspondingly, our recent work has shown that the average step size for micellar foam films is comparable to the intermicellar distance in bulk d measured for salt-free micellar solutions using small-angle X-ray scattering (SAXS) . This agreement appears to be consistent with the studies that assume that salt-free solutions of micelles and nanoparticles structure in confinement in an analogous manner.…”
Section: Introductionmentioning
confidence: 99%
“…We consider stratifying foam films as the model system for examining the influence of these oscillatory structural forces. Though an interplay between Π OS ( h ) and capillarity is expected to determine the nanoscopic topography of stratifying foam films, the lack of suitable techniques for foam films was a longstanding challenge that Sharma and co-workers addressed by introducing the interferometry digital imaging optical microscopy (IDIOM) protocols. , The exquisite pixelwise thickness maps (with sub-nanometer resolution) obtained using IDIOM and theoretical estimates made with thin-film equation ,,,,, amended with Π OS ( h ) show that the topographical features revealed by quantifying thickness transitions and variations are correlated with intermicellar interactions, confinement effects, and the magnitude and periodicity of the resulting Π OS ( h ). , , , ,, Yilixiati et al contrasted the change in topography and step size on increasing either salt or surfactant concentration for stratifying foam films comprising sodium dodecyl sulfate (SDS), a commonly used anionic surfactant. In both cases, step size decreases.…”
Section: Introductionmentioning
confidence: 99%